Effects of wall-located heat barrier on conjugate conduction/natural-convection heat transfer and fluid flow in enclosures - Hakyemez, Erinc; Mobedi, Moghtada; Öztop, Hakan Fehmi (Taylor & Francis Inc, 2008)
The effects of a heat barrier, located in the ceiling wall of an enclosure, on conjugate conduction/natural convection are investigated numerically. The vertical walls of the enclosure are differentially heated and the horizontal walls are adiabatic. Heatline technique is used to visualize heat transport. The variations of average Nusselt number, dimensionless heat transfer rate through the ceiling wall, and dimensionless overall heat transfer rate are studied. Calculations are performed for different Rayleigh numbers (10(3) <= Ra <= 10(6)), thermal conductivity ratios (K = 100), dimensionless locations of the heat barrier (0 < X-h < 1), and two dimensionless ceiling wall thicknesses (D = 0.05 and D = 0.20). For high thermal conductivity ratio (K = 100), the heat barrier considerably reduces the dimensionless overall heat transfer rate. The effect of the heat barrier on dimensionless heat transfer rate through the enclosure increases as the Rayleigh number decreases. For low Rayleigh number (i.e., Ra = 10(3)), a location exists in the ceiling wall for which the dimensionless overall heat transfer rate is minimum.
Keywords: Natural-Convection; Square Enclosure; Visualization